Pengujian Black Box pada Aplikasi Daftar Peserta Vaksinasi COVID-19 Berbasis Situs Web dengan Metode Equivalence Partitions - Syahputra, Muhammad Arvy; Maulana, Nanda Risky; Fajri, Rahmad Danil; Zaki, Teuku Raja Muhammad; Yulianti, Yulianti (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
Making an application has many stages and processes, after the application has been formed it is necessary to have a series of tests on the application to ensure that whether the application can run well or not. If an application does not go through the testing stage, it will be difficult to know how the quality of the application is and it will not be known whether there are obstacles or not when the user uses it. In the COVID-19 Vaccination Participant List application, if this problem occurs, the admin will find it difficult to enter participant data and also Health Facilities and this may result in incorrect data input. To solve this problem, the author will test using the black box testing method. Black box testing or better known to many people through the term functional testing and is a software testing method used to test software where the tester does not know or does not know the internal structure of the application code or program. In a series of tests that are applied to the program the tester knows what the program must do, but the tester does not have knowledge of how the program fulfills the commands that have been given. From the data from the website testing, the COVID-19 Vaccination Participant List Website is ready to be recommended and run for the sake of recording COVID-19 vaccination participants in Indonesia.